Natural resources management for sustainable agriculture and environment - Deb, D. L.n. (New Delhi Angkor Publishers, 1994)
Contributed research papers in the nature of survey of literature; in the Indian context.
Includes bibliographical references.
Keywords: Conservation of natural resources -- India; Natural resources -- India -- Management; Sustainable agriculture -- India